(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
Digitalisation rapidly changes labor market needs in the contemporary era and therefore, vocational education systems must adapt their lessons and introduce new technology. This article will discuss six pedagogical approaches to digital skill development in vocational education students: Competency-Based Training (CBT), Project-Based Learning (PBL), Blended Learning, Simulation-Based Training, Work-Based Learning (WBL), and the Scaffolding Method. The research results indicate that Competency-Based Training ensures a learning process oriented towards the outcomes in line with industry standards. Project-Based Learning develops critical thinking, collaboration, and innovation capabilities. Blended Learning provides flexibility and effectiveness. Simulation-Based Training enables practical skill formation in safe environments. Work-Based Learning offers opportunities for gaining real professional experience. Based on Vygotsky’s Zone of Proximal Development theory, the Scaffolding Method develops independent learning abilities through gradual support. These strategies are further discussed in terms of how to integrate them in order to facilitate the general development of digital skills. In this article, the authors offer suggestions towards its integration and practical application.